Angular dependent magnetothermopower of α-(ET)2KHg(SCN)4: Органические проводники - Krstovska*, D.; Steven, E.; Choi, E.S.; Brooks, J.S. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2011)
The magnetic field and angular dependences of the thermopower and Nernst effect of the quasi-twodimensional (q2D) organic conductor α-(ET)2KHg(SCN)4 are experimentally measured at temperatures below (4 K) and above (9 K) the transition temperature to fields of 31 T. In addition, a theoretical model which involves a magnetic breakdown effect between the q1D and q2D bands is proposed in order to simulate the data. Analysis of the background components of the thermopower and Nernst effect imply that at low temperatures, in the CDW state, the properties of α-(ET)2KHg(SCN)4 are determined mostly by the orbits on the new openFermi sheets. Quantum oscillations observed in the both thermoelectric effects, at fields above 8 T, originateonly from the α orbit.